131k views
1 vote
What is the answer to this problem.

What is the answer to this problem.-example-1

1 Answer

4 votes

Answer:


2a^2 + 3x - 2a

Explanation:


(6a^2 + 3x) - (4a^2 + 2a) =

The first set of parentheses is unnecessary and can be removed.


= 6a^2 + 3x - (4a^2 + 2a)

To remove the second set of parentheses, you must distribute the negative sign to its left as if it were a -1 multiplying the quantity inside the parentheses.


= 6a^2 + 3x - 1(4a^2 + 2a)


= 6a^2 + 3x - 4a^2 - 2a

Now combine like terms. Like terms are terms with the same variable part.


= 2a^2 + 3x - 2a

User Reinto
by
4.7k points